Human Capital Accumulation at Work : Estimates for the World and Implications for Development - Jedwab, Remi; Romer, Paul; Islam, Asif; Samaniego, Roberto (World Bank, Washington, DC, 2021)
In this paper, the authors: (i) study wage-experience profiles and obtain measures of returns to potential work experience using data from about 24 million individuals in 1,084 household surveys and census samples across 145 countries; (ii) show that returns to work experience are strongly correlated with economic development—workers in developed countries appear to accumulate twice more human capital at work than workers in developing countries; (iii) use a simple accounting framework to find that the contribution of work experience to human capital accumulation and economic development might be as important as the contribution of education itself; and (iv) employ panel regressions to investigate how changes in the returns over time correlate with several factors such as economic recessions, transitions, and human capital stocks.